Strategic vaccination responses to Chikungunya outbreaks in Rome: Insights from a dynamic transmission model. - Albertus Constantijn Sloof; Martijn Boer; Gerard T Vondeling; Adrianne M de Roo; Juan Carlos Jaramillo; Maarten J Postma (PLoS Neglected Tropical Diseases)
Background Chikungunya virus (CHIKV) outbreaks, driven by the expanding habitat of the Aedes albopictus mosquito and global climate change, pose a significant threat to public health. Our study evaluates the effectiveness of emergency vaccination using a dynamic disease transmission model for a potential large-scale outbreak in Rome, Italy. Methods The model incorporates a susceptible-exposed-infected-recovered (SEIR) framework for human and mosquito populations, taking into account temperature-dependent mosquito lifecycle dynamics, human-mosquito interactions, and various vaccination scenarios. Findings Results indicate that emergency vaccination could significantly mitigate the impact of a CHIKV outbreak. Without vaccination, an outbreak is estimated to infect up to 6.21% of Rome's population, equating to approximately 170,762 individuals. Implementing rapid vaccination after detecting the virus in ten individuals and achieving 40% coverage could reduce infection rates by 82%, preventing 139,805 cases. Scenario and sensitivity analyses confirm that even with lower vaccination coverage rates, significant benefits are observed: at 10% coverage, the number of infections drops to 115,231, and at 20% coverage, it further reduces to 76,031. These scenarios indicate prevention of approximately 33% and 55% of infections, respectively. Conclusions The findings highlight the critical role of timely vaccination interventions in outbreak settings, demonstrating that even modest coverage levels can markedly decrease the spread of CHIKV. This study underscores the importance of preparedness, early detection and adaptive response capabilities to manage emerging infectious diseases in urban centres, advocating for strategic vaccine stockpiling and rapid deployment mechanisms to enhance public health outcomes.